Efficiency improvement of an axial flow propeller pump installed at Kudumpattupadam kole padavu, Thrissur - AYISHA MANGAT NITHIN J. G SARANYA R. NATH; Dr. Jayan P. R (Guide) (Tavanur 2014 Department of Farm Power Machinery and Energy)
Efficiency improvement of an axial flow propeller pump installed at Kudumpattupadam kole padavu, Thrissur
Efficiency improvement of an axial flow propeller pump installed at Kudumpattupadam kole padavu, Thrissur